Application of reactor dosimetry techniques for source term validation in F-18 production with a medical cyclotron - Konheiser Joerg; Mueller Stefan E. (EPJ Web of Conferences)
Imaging techniques such as positron emission tomography need radionuclides that can be produced with cyclotrons. The involved nuclear reactions mostly produce neutron and gamma radiation, which must be shielded. In order to be able to determine the required thickness of the shielding for a newly bought medical cyclotron, corresponding radiation protection calculations were carried out. The necessary neutron source term was supplied by the manufacturer. To verify this source term, additional source terms were calculated with the MCNP6 and the FLUKA code packages. The results with the source, on base of code internal nuclear models, produced comparable results, but the neutron yield with the source supplied by the manufacturer turned out to be lower by a factor of about 5. To validate the results, experiments were carried out on an already existing cyclotron. Neutron fluence was measured with standard monitors which are used in reactor dosimetry. The experiments were performed during regular 18F production. Activities of the nuclides were measured by gamma spectroscopy and compared with the calculated activities.